Development and surgical application of a custom implant that enables a vertical vector of mandibular distraction. (October 2020) - Gonzalez Alvarez, Alba; Dovgalski, Lawrence; Evans, Peter Ll.; Key, Steven
Hemifacial microsomia is a congenital malformation that involves the underdevelopment of the mandible and the ear leading to facial asymmetry. Distraction osteogenesis is the gold standard surgical procedure for severe cases of hemifacial microsomia in which two sectioned bone parts are lengthened gradually to promote bony infill. The final shape of the bone depends on the position of the distractor and the vector of distraction. This article presents a complex clinical case of a 7-year-old patient with severe hemifacial microsomia that required distraction to correct mandibular asymmetry. Digital technology was applied to virtually plan the surgery pre-operatively. Optimal symmetrisation required a vertical vector of distraction that none of the 'off-the-shelf' distractors could provide. Consequently, a three-dimensional printed titanium implant was designed as a spacer to be attached to the inferior plate of a standard distractor, allowing the achievement of a vertical vector. By adding the spacer, the inferior footplate of the distractor was not directly fixed to bone and the vector of distraction was not dictated by the anatomical contour of the patient but by the shape of the spacer. Surgical guides were created to translate the virtual plan to the operating room. The guides prevented potential damage to tooth buds and the inferior alveolar nerve. This article describes the three-dimensional computer-aided design and additive manufacture of the custom devices that delivered the following: (1) symmetrisation of the mandible after distraction surgery without manipulation of the healthy side of the mandible; (2) a feasible and safer surgical solution; and (3) an innovative method that enables a wider range of vectors of distraction, bringing new prospects to the treatment of distraction osteogenesis in the future.